Effectiveness of bed bath methods for skin integrity, skin cleanliness and comfort enhancement in adults: A systematic review - Issei Konya; Kotone Nishiya; Rika Yano (Wiley, 2021)
Abstract Aim To evaluate the effectiveness of bed bath methods for skin integrity, skin cleanliness and comfort enhancement in adults. Design A systematic review based on the PRISMA guidelines. Methods We searched for quantitative studies published between 2004-2020, using the PubMed, MEDLINE and CINAHL. The remaining 25 studies were appraised by the JBI tool. Results Only four of the included studies were of high quality. Studies of above moderate quality demonstrated that disposable towels were as effective as cotton towels for skin lesions and bacterial removal. Applying a hot towel maintained the skin barrier function and provided warmth; cotton towels were effective for cleaning even with weak pressure, and post‐bed bath moisturizer treatment contributed to skin integrity. Conclusion Although various methods have been examined, the available evidence is inadequate for establishing best practices. It is necessary to verify empirical research with rigorous methodology involving elderly inpatients and to develop instruments that measure patients' comfort.